Petrography and geochemistry of hydrothermal breccias hosted in the Schrikkloof Formation (Rooiberg Group), north of Modimolle, South Africa - Lenhardt, Nils (University of Pretoria, 2023)
Thesis (MSc (Geology))--University of Pretoria, 2023.